Management of Dry Eye Syndrome - Siddiqui, Zahid Kamal (Pakistan Journal of Ophthalmology, 2008)
Dry eye syndrome (DES) is a common disorder where there is a qualitative or quantitative deficiency in the tear film. It is largely undiagnosed and mistreated in Pakistan1. The diagnosis can be improved by identification of the symptoms namely; dry sensation, burning sensation, foreign body sensation (Rarrak), photophobia, and blurred vision are common in patients with dry eye. These symptoms are often exacerbated in smoky and/or dry environments like kitchen, busy city streets and at out door work. The symptoms can also be precipitated by acts of visual concentrations like watching TV, reading and excessive computer use. Sometimes a patient with DES presents with paradoxical watering which is named as ‘Wet Dry Eye’1.